ANALISIS IMPLIKATUR WACANA PERCAKAPAN DALAM NOVEL “MASIH ADA HARI ESOK KARYA DANIEL STEEL”: ANALISIS IMPLIKATUR WACANA PERCAKAPAN - DAIRI SAPTA RINDU SIMANJUNTAK (BASIS (Bahasa dan Sastra Inggris), 2017)
Language is a communication tool used by every human being in every aspect. without language there would not be a good relationship between people. Language knowledge is considered as one of the thought and understanding. The language can be found everywhere characterized by the use of symbols both oral and written. In the event of communication, speaker and hearer often communicate using implicit intent, meaning different from what is disclosed is called implicatures. The purpose of this study was to describe the conversation discourse containing implicatures. as for the formulation of the problem in this study is how the implicature use when communicating between speaker and hearer in the novel “Masih Ada Hari Esok" by Daniel Steel?. This paper is the study of literature by using descriptive method. After the author discusses the problems in this study , the results obtained is that in the novel "Masih Ada Hari Esok" by Daniel Steel containing conversational implicature there